Lipoprotein Metabolism and Atherogenesis 2000
DOI: 10.1007/978-4-431-68424-4_14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of troglitazone on plasma lipid metabolism and lipoprotein lipase

Abstract: Aims To clarify how troglitazone, an insulin-sensitizing agent, affects lipid metabolism and postheparin plasma lipoprotein lipase (LPL). Methods Fifteen patients (3 male, 12 female) (the average age 62±7 years; the mean body mass index (BMI) 25±3 kg/m 2 ) were recruited for this study. The serum lipids and postheparin plasma lipoprotein lipase (LPL) mass before and 4 weeks after oral administration of troglitazone (200 mg day −1 ) were measured. A mouse preadipocyte cell line, 3T3-L1, was incubated with trogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
5
9
0
Order By: Relevance
“…The men group showed a higher serum TG and lower HDL-C levels along with lower plasma LPL mass than did women. Troglitazone, an insulin sensitizer and now out of market in Japan, was reported to cause an increase in pre-heparin LPL mass [32], which is consistent with our study showing this agents increased LPL mass in PHP [33].…”
Section: Serum Lpl Mass In Type 2 Diabetes Mellitussupporting
confidence: 92%
“…The men group showed a higher serum TG and lower HDL-C levels along with lower plasma LPL mass than did women. Troglitazone, an insulin sensitizer and now out of market in Japan, was reported to cause an increase in pre-heparin LPL mass [32], which is consistent with our study showing this agents increased LPL mass in PHP [33].…”
Section: Serum Lpl Mass In Type 2 Diabetes Mellitussupporting
confidence: 92%
“…Stepwise multiple regression analysis confirmed that the association of the Pro12Ala polymorphism with LPL activity was independent of potential confounding factors such as age, BMI, insulin levels, hypertension, and pack-years (data not shown). Our data of the association of a PPAR-␥2 polymorphism that is characterized by lower transcriptional activity with lower LPL activity in vivo supports the recent observation that treatment with troglitazone, a PPAR-␥ agonist, increases LPL concentration in postheparin plasma (12). …”
supporting
confidence: 89%
“…This observation has been in line with the previous reports on the effects of this compound on LPL activity in PHP (26,27). Troglitazone, an insulin sensitizer, has also been reported to cause an increase in pre-heparin LPL mass (29), which is consistent with our study showing this agent increased LPL mass in PHP (30). In contrast, atorvastatin did not produce an increase in pre-heparin LPL mass in hyperlipidemic subjects, despite causing a substantial reduction in serum TG level (31), which may be related to the fact that the main mechanisms for the reduction in serum TG by this agent are the inhibition of the production and secretion of VLDL from the liver.…”
Section: Effects Of Several Lipid-lowering Agents On Pre-heparin Lpl supporting
confidence: 92%